Heart Lesions in Rheumatological Diseases (Texas Journal of Medical Science, 2022)
The study presents the results of a comparative echodopplercardiographic study of heart lesions in rheumatological diseases (rheumatoid arthritis, systemic lupus erythematosus, chronic rheumatic heart disease, systemic scleroderma and chronic spondylitis). It is shown that the frequency of heart and pericardial valve damage depends on the type of disease, which must be taken into account when ultrasound examination of the heart of patients with heumatological diseases. Rheumatic heart disease is a disease that affects the heart valves or forms a heart defect. As a result, there is heart failure, stenosis, heart rhythm disorder and other negative pathologies. It is well known that patients with rheumatological diseases (RH) — such as systemic lupus erythematosus (SLE), systemic scleroderma (SSD), ankylosing spondylitis (AS), rheumatoid arthritis (RA), are characterized by a significantly higher level of cardiovascular morbidity and mortality compared to the indicators in the general population. It has been shown that patients with RS are characterized by a faster progression of the atherosclerotic process and a high incidence of thrombosis, which cannot be fully explained by the influence of traditional factors risk of cardiovascular pathology. Therefore, a number of authors have suggested the role of inflammation as a link between RH and atherosclerosis, damage to target organs, where inflammatory mediators and pro-inflammatory cytokines act as intermediaries. At the same time, the profile of inflammatory markers differs depending on the type of RH, which may manifest itself in the features of target organ damage, however, this assumption has not been practically investigated before.